Glycosylation sites of vesicular stomatitis virus glycoprotein. - Robertson, J S (1976)
Detailed analysis on DEAE-Sephadex of the tryptic digestion products of the glycoprotein from vesicular stomatitis virus grown in HeLa suspension cultures revealed the presence of two major and several minor sugar-labeled species. The minor tryptic glycopeptides were converted to one of the two major glycopeptide species by treatment with neuraminidase. Thus, vesicular stomatitis virus glycoprotein contains only two oligosaccharide side chains that are heterogeneous in their sialic acid content.